Analisis Karakteristik Rumah Tangga Miskin Penerima Program Keluarga Harapan dan Penerima Keluarga Harapan Sekaligus Bantuan Pangan Non-Tunai di Indonesia - Wahyuni, Widya Sri; Putra, Febriandi Prima (Jurnal Informatika Ekonomi Bisnis, 2025)
This study analyzes the characteristics of poor households receiving the Family Hope Program (PKH) and those receiving both PKH and Non-Cash Food Assistance (PKHBPNT) in Indonesia in 2023. Data were obtained from the raw data of the March 2023 National Socio-Economic Survey (Susenas), focusing on 27,747 poor households. Descriptive analysis and binary logistic regression were used to identify factors influencing the receipt of assistance. The results show that the presence of school-age children, elderly members, and persons with disabilities significantly increases the likelihood of poor households receiving PKH and PKHBPNT. Additionally, poor households in rural areas are more likely to receive assistance compared to those in urban areas. However, several indicators, such as the presence of toddlers, the occupation of the household head, and per capita floor area, do not have a significant influence. These findings indicate biases in the distribution of assistance, where poor households with more complex living conditions tend to receive assistance more frequently. This study recommends improving the selection mechanisms and data updating to enhance the targeting accuracy of social assistance programs, thereby increasing their effectiveness in reducing poverty and improving community welfare.